Quality and women's satisfaction with maternal referral practices in sub-Saharan African low and lower-middle income countries: a systematic review - Edward Kwabena Ameyaw; Carolyne Njue; Nguyen Toan Tran; Angela Dawson (BMC, 2020)
Abstract Background sub-Saharan African Low and Lower-Middle Income Countries (sSA LLMICs) have the highest burden of maternal and perinatal morbidity and mortality in the world. Timely and appropriate maternal referral to a suitable health facility is an indicator of effective health systems. In this systematic review we aimed to identify which referral practices are delivered according to accepted standards for pregnant women and newborns in sSA LLMICs by competent healthcare providers in line with the needs of pregnant women. Methods Six electronic databases were systematically searched for primary data studies (2009-2018) in English reporting on maternal referral practices and their effectiveness. We conducted a content analysis guided by a framework for assessing the quality of maternal referral. Quality referral was defined as: timely identification of signal functions, established guidelines or standards, adequate documentation, staff accompaniment and prompt care by competent healthcare providers in the receiving facility. Results Seventeen articles were included in the study. Most studies were quantitative (n = 11). Two studies reported that women were dissatisfied due to delays in referral processes that affected their health. Most articles (10) reported that women were not accompanied to higher levels of care, delays in referral processes, transport challenges and poor referral documentation. Some healthcare providers administered essential drugs such as misoprostol prior to referral. Conclusions Efforts to improve maternal health in LLMICs should aim to enhance maternity care providers' ability to identify conditions that demand referral. Low cost transport is needed to mitigate barriers of referral. To ensure quality maternal referral, district level health managers should be trained and equipped with the skills needed to monitor and evaluate referral documentation, including quality and efficiency of maternal referrals. Trial registration Systematic review registration: PROSPERO registration CRD42018114261 .